2007
DOI: 10.1159/000108596
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Prolonged and Exclusive Breast-Feeding on Dental Caries in Early School-Age Children

Abstract: To study the effects of prolonged and exclusive breast-feeding on dental caries, we followed up children participating in the Promotion of Breastfeeding Intervention Trial (PROBIT), a cluster-randomized trial of a breast-feeding promotion intervention based on the WHO/UNICEF Baby-Friendly Hospital Initiative. A total of 17,046 healthy, mother-infant breast-feeding pairs were enrolled from 31 Belarussian maternity hospitals and affiliated polyclinics, of whom 13,889 (81.5%) were followed up at 6.5 years. At fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 27 publications
4
35
1
2
Order By: Relevance
“…However, children living in poverty, Mexican American children and those exposed to maternal smoking behaviors were at increased risk for poor oral health in the early years 35. Other investigators have confirmed these findings, and have identified milk-bottle feeding at night (in which the sweetened liquid remains in contact with the developing dentition) as the most significant determinant of ECC 36,37…”
Section: Parenting Practicesmentioning
confidence: 85%
“…However, children living in poverty, Mexican American children and those exposed to maternal smoking behaviors were at increased risk for poor oral health in the early years 35. Other investigators have confirmed these findings, and have identified milk-bottle feeding at night (in which the sweetened liquid remains in contact with the developing dentition) as the most significant determinant of ECC 36,37…”
Section: Parenting Practicesmentioning
confidence: 85%
“…≥8 or ≥13 months) and have featured populations in which breastfeeding to age 2 years is uncommon, such as in Germany [42], Italy [17], and the United States [18]. A large hospital-based breastfeeding promotion intervention in Belarus did not affect caries prevalence at age 6 years [43]; however, the study did not directly compare caries outcomes among children who were or were not breastfed for extended durations (e.g. ≥24 months), which was an uncommon behavior in that trial population.…”
Section: Discussionmentioning
confidence: 99%
“…Caries reduction was not found following peer-led "social support" for recommended feeding practices in London (Scheiwe et al, 2010). In a large hospitalbased cluster-randomized trial of breastfeeding promotion, no caries effect was reported at age 6 yrs (Kramer et al, 2007). Study strengths included randomization and the ability to compare results with the São Leopoldo intervention, which differed by implementation scheme.…”
Section: Discussionmentioning
confidence: 99%